The Effects of Product Placement in Fictitious Literature on Consumer Purchase Intention. Issue 11 (November 2016) - Barnhardt, Terrence M.; Manzano, Isabel; Brito, Maria; Myrick, Melissa; Smith, Steven M.
ABSTRACT: Three experiments tested whether brand‐name products placed in a short story would be more often selected when two identical products with different brand names were presented in either a picture or text format in forced choice purchase intention and placement recognition tests. In Experiments 1a and 1b, there was no significant influence of product placement in a pictorial purchase intention task. However, in Experiments 2a and 2b, a reliable and equal level of recognition memory was observed, regardless of whether the products were presented in a picture (Exp. 2a) or text (Exp. 2b) format. In Experiment 3, the products were presented in a text format in the purchase intention task and participants more often and more quickly chose the brand‐name product from the story. At a practical level, these results suggest some limits to the usefulness of product placement in text.